Drug-induced liver injury after anti tuberculosis drugs administration, how to diagnose? a case report - Ratnansari Giri, Ray; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
Drug-induced liver injury (DILI) is a liver injury caused by various drugs, herbs, or other xenobiotics, which causes abnormalities in liver tests or liver dysfunction in the absence of other causes of liver damage. The most common causative drugs are antituberculosis drugs (ATDs), anti-infective drugs, and natural herbal medicines. The diagnosis of DILI can be difficult due to the lack of specific signs, symptoms and tests and is partly a diagnosis based on exclusion. In this case report, we will discuss how to diagnosis DILI TB and causative assessment using RUCAM score. A male, 64 years old, has complained of weakness since 1 week ago and worsened since 1 day ago. The patient also felt persistent nausea for 1 week, so his eating and drinking decreased. Besides, he complained getting abdominal pain, especially in the upper right region and heartburn. The patient has been on first category of TB treatment since 20 days ago. Chest X-ray showed Lung TB with infiltrate in multiple cavities. Abdominal ultrasound showed no abnormality. The patient was discharged from our hospital after 6 days of hospitalization. DILI remains a diagnosis of exclusion based primarily on a detailed history and judicious use of blood tests, hepatobiliary imaging, and liver biopsy. The Roussel Uclaf causality assessment method (RUCAM) system is an assigning point for clinical, biochemical, serologic and radiologic features of liver injury. We use RUCAM score to make an assessment that show the likelihood of the hepatic injury due to a specific medication.